(3Yjhf GdeYGQa hafhf CNHGQ GdNdGFas - (3eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj , TgGH GdOjf CHh YHO Gddg,J (B454 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeHJOi cd TF GdhGQK GdeYjO cd Mi gPG cJGH CLeY ajg HeTjFI Gddg hYhfg s
(3BNQgG (B:s
(3BNQ GdehLhO efgG GdcdGe Ydi fSH eMeO QShd Gddg s
(3GfXQ GdbSe GdChd Qbe (B347 (3hGdbSe GdKGfi Qbe (B747s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B343 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B220 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs